Santa Fe Trail (Goodtimes Home Video, 1984)
Leavenworth, Kansas, where the railroad and civilization ended and the Santa Fe Trail began. This exciting pre-Civil War western depicts slavery until his capture at Harpers Ferry. This powerful film dramatizes the origin of the bloody period of history. Excellent performances and exciting action scenes as Jeb Stuart (Flynn) and his co-horts go after John Brown (Raymond Massey). Reagan plays Flynn's West point classmate and romantic rival, George Armstrong Custer.